Blooms of Cochlodinium polykrikoides (Gymnodiniaceae) in the Gulf of California, Mexico - Gárate-Lizárraga, I. (2004)
Cochlodinium polykrikoides was the species responsible for the discoloration that occurred between September 15th and 27th, 2000 in a shallow coastal lagoon located in the southern part of the Bahía de La Paz, on the west side of the Gulf of California. Blooms of C. polykrikoides were observed four days after two rainy days with a seawater temperature of 29 to 31°C. Nutrient concentration ranges during the bloom were 0.165- 0.897 μM NO2+NO3, 0.16-3.25 μM PO4, and 1.0-35.36 μM SiO4. Abundance of C. polykrikoides ranged from 360 x 103 to 7.05 x 106 /cells l-1. Biomass expressed in terms of chlorophyll a was high, ranging from 2.7 to 56.8 mg/m3. A typical dinoflagellate pigment profile (chlorophyll a and c, peridinin, diadinoxantin, and β-carotene) was recorded. In this study, the red tide occurred in front of several fish and shrimp-culture ponds. No PST toxins were found in the samples. However, 180 fish were found dead in the infected fish-pond; the gills were the most affected part. C. polykrikoides is a cyst-forming species that recurs in this area. New blooms were observed in November 2000 and September-November 2001 in the same area. Anthropogenic activities, such as eutrophication caused by water discharge in this shallow lagoon, and nutrient enrichment in the culture ponds, as well as effects from precipitation and wind stress, could have favored the outbreak of this dinoflagellate.